Interaksi Simbolik Pada Pertunjukan Musik Keroncong oleh Orkes Keroncong Gunung Jati New Musik di Stasiun Tawang Semarang - Rinaldhi Eka Kurnia Putra; Abdul Rachman; Eko Raharjo; Suharto Suharto (Gondang: Jurnal Seni dan Budaya, 2021)
The Gunung Jati New Music Keroncong Orchestra is a keroncong orchestra that regularly performs keroncong music at Tawang Station Semarang. During the keroncong music performance there are various kinds of symbolic interactions between the players and also with the audience. The purpose of this study was to determine how the symbolic interaction in keroncong music performances by the Keroncong Gunung Jati New Music Orchestra. The research method used is qualitative. The data collection techniques used were observation, interview and documentation. The data collected through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the symbolic interaction at the Keroncong Gunung Jati New Musik orchestra performance at Tawang Semarang station included a sawer box as a place for the audience to give sawer money as a form of appreciation. Symbolic interaction between the players and the players, namely during the performance the players give each other song chord codes with gestures of limbs such as finger movements, head nods, speech, winks. And symbolic interactions between the players and the audience in the form of hand movements, head nods, clapping, and sawer money. From these findings it can be concluded that the symbolic interaction that occurs is as an interaction that aims to find chemistry between players and between players and the audience so that the keroncong music performance runs well and smoothly so that the players and the audience are satisfied with their appearance and as an attraction of the Keroncong Orchestra. Gunung Jati New Musik in attracting public interest in keroncong music itself.